Diversity of VIr’s collection of Lupinus angustifolius L. in the inf lorescence color - E. V. Vlasova; G. P. Egorova (Труды по прикладной ботанике, генетике и селекции)
Background. The phenotypic structure of Lupinus angustifolius L. is dynamically expanding due to genetic recombinations and mutagenesis. Therefore, the existing concepts of the inflorescence color diversity in narrowleaf lupine need regular updating.Materials and methods. Research materials consisted of 887 narrowleaf lupine accessions from the VIR collection. Their morphological descriptions were made in 2009–2023 during field trials under the conditions of Moscow Province, Russia. Longterm observations made it possible to evaluate probable color modifications in inflorescences under varying weather conditions.Results. The lupine gene pool was divided into 15 biotypes differing in the anthocyanin pigmentation of separate inflorescence parts, such as the vexillum, wings, and keel, as well as the inflorescence axis. Individual color features of cotyledons, leaves, stem, and seeds also characterized the biotypes. Phenotypic characteristics of lupine biotypes were compared with diagnostic traits of intraspecific taxa and known genes for flower color.Conclusion. Three new varieties and six new subvarieties were marked out for narrowleaf lupine. Probable carriers of genes responsible for the flower’s basic color: roseus (fco 1), violaceus (fco 3), albus (fco 4), and leucospermus (fco 21, fco 22), and its modifications: Supercoeruleus, dispersus, discolor, and albiflorus, were identified. Descriptions of some biotypes failed to agree with the data on any known gene’s phenotypic expression, which attested to the presence of new mutations, recombinations, or unstudied gene associations.